2020
DOI: 10.1021/acsami.9b19004
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Very Low Energy Electrons in Tin-Based Molecular Resists for Extreme Ultraviolet Nanolithography

Abstract: Extreme ultraviolet (EUV) lithography (13.5 nm) is the newest technology that allows high-throughput fabrication of electronic circuitry in the sub-20 nm scale. It is commonly assumed that low-energy electrons (LEEs) generated in the resist materials by EUV photons are mostly responsible for the solubility switch that leads to nanopattern formation. Yet, reliable quantitative information on this electron-induced process is scarce. In this work, we combine LEE microscopy (LEEM), electron energy loss spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 47 publications
(109 reference statements)
0
72
1
Order By: Relevance
“…During the scattering, more molecules can be ionized so that secondary electrons are generated, which have a broad distribution of kinetic energies in the 0-80 eV range. 14 Therefore, the chemistry induced by EUV photons is the result of the electron-induced chemistry [17][18][19] and the chemical a Advanced Research Center for Nanolithography, Science Park 106, processes that the ionized molecules undergo. Furthermore, the probability of absorbing EUV photons by molecules is mainly determined by their elemental composition rather than by the selection rules based on the characteristics of the frontier molecular orbitals that apply in photochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…During the scattering, more molecules can be ionized so that secondary electrons are generated, which have a broad distribution of kinetic energies in the 0-80 eV range. 14 Therefore, the chemistry induced by EUV photons is the result of the electron-induced chemistry [17][18][19] and the chemical a Advanced Research Center for Nanolithography, Science Park 106, processes that the ionized molecules undergo. Furthermore, the probability of absorbing EUV photons by molecules is mainly determined by their elemental composition rather than by the selection rules based on the characteristics of the frontier molecular orbitals that apply in photochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Haitjema et al studied the chemical behavior observed in tin oxo cage materials under UV exposure to get clues that could also be of use for determining the EUV imaging chemistry [114]. Further insights on tin oxo cages chemistry at EUV was provided in the recent work by Bespalov where the influence of electron energy was studied [40]. The main results from this study are depicted in Figure 9.…”
Section: Inorganic Resistsmentioning
confidence: 72%
“…In this respect, since photoelectrons and secondary electrons resulting from ionizing radiation were recognized to play the main role in solubility changing reactions [ 37 ], attention was drawn to the fundamentals of electron-induced chemistry known from other scientific fields as described for instance in [ 38 , 39 ]. Recently a study on the role of low energy electrons in a tin containing resist was published [ 40 ] and revealed their important role in resist chemistry. Similar studies are expected to dramatically improve the understanding of the resist chemistries at EUV.…”
Section: Chemical Directions For Highly Sensitive Resists At Euvmentioning
confidence: 99%
See 1 more Smart Citation
“…We are interested in alkyltin clusters for nanolithography, due to the radiation sensitivity of the alkyl ligands, high EUV absorption of Sn, and the precise and small features enabled by molecular clusters [25–27] . The family of alkyltin Keggin ions is unique in that only the β and γ isomers have been identified by single‐crystal x‐ray diffraction.…”
Section: Introductionmentioning
confidence: 99%